Avaliação do reaproveitamento de membranas cerâmicas de alta pureza produzidas a partir de α - Al2O3 para incorporação em cerâmica vermelha - Heron Viterbre Debique Sousa (2023)
The red ceramic industry is a fundamentally important sector for the construction industry. Therefore, products of high quality are increasingly demanded, in such a way that they perform excellently in their intended function and also meet the minimum standards required for commercialization. One of the methods being used to obtain products with better properties is the use of additives that are incorporated into the clay (the raw material of red ceramics). Often, these additives are residues originating from industrial processes which mean they have a wide variety in chemical composition, considering the various stages they can be processed through. In this perspective, the study aimed to evaluate the incorporation of ceramic membrane residues produced from high-purity α - Al2O3 in red ceramics, with the intention of containing the variables that would be caused by the instability of the chemical composition of industrial residues. The experimental procedures consisted of the chemical and mineralogical characterization of the clay and the residue, and the physical-mechanical characterization of the products produced from the mentioned raw materials. Test specimens were made by extrusion, using an extruder with a pressure of 4 MPa, with a vacuum maintained between 380 e 400 mmHg. The variations in the composition of the ceramic mass were 2 %, 4 % and 6 % addition of α - Al2O3 relative to the amount of clay, and a mixture was prepared without the incorporation of the residue. The clay masses were sintered in a crucible furnace at different temperatures: 800 ◦C, 900 ◦C and 1000 ◦C. The characterization of the raw materials was done using particle size by sieving, X-ray fluorescence, X-ray diffraction, thermal analyses. The evaluated physical-mechanical properties were: water absorption, drying linear shrinkage, firing linear shrinkage, apparent porosity, apparent specific mass, loss on ignition, and mechanical flexural strength. Scanning electron microscopy analysis was performed on the fracture surfaces of the test specimens. The results showed that kaolinitic clay with quartz and alumina residue, both of coarse granulometry, interact well during mixing and shaping. The sintering temperature was crucial, affecting water absorption, linear shrinkage, and the mechanical properties of the products. The addition of up to 6 % alumina residue modestly improved mechanical strength without significantly altering the overall properties. This finding suggests that the use of alumina waste is viable, offering environmental and economic benefits, as well as contributing to sustainable practices in the ceramic industry.